Prevalence of Gastro-Intestinal Parasites in Chickens Sold in Some Major Markets in Greater Accra, Ghana - Ayeh-Kumi, P.F.; Gerald, Larbie Nii-dodoo; Olu-Taiwo, Michael; Akua , Forson Obeng (International Journal of Poultry Science, 2016)
Gastrointestinal parasitic infections in chicken production industry are known to be one of the factors responsible for the high mortality rate in poultry farming in Africa. This study aimed to determine the prevalence of gastrointestinal parasites in chickens sold in major markets in Accra, Ghana. A cross-sectional study was carried out with 152 alimentary tracts of chicken randomly collected from the chicken dressing units from major markets (Achimota, Agbogboloshie, Nungua, Kaneshie and Dansoman markets) in Accra, Ghana. The samples were examined for gastrointestinal parasites by examination of fecal samples of birds, collection of parasites from different part of gastrointestinal tract and examination of the collected parasites by standard parasitological techniques followed by morphological identification as far as possible up to the species level. Out of 152 chickens examined from the five markets, 121(79.9%) chickens were found to be infected with gastrointestinal parasites. The chickens were found to be commonly infected with Capillaria spp (46.1%), Heterakis gallinarum (39.5%) and Ascaridia galli (36.9%). Out of the 121 chickens examined, 63.63% had mixed infection. No trematodes were encountered in this present study. The different market locations did not have any significant influence on the prevalence of the different gastrointestinal parasites detected. However, chickens from Nungua market were found to have the highest level (90%) of gastrointestinal parasite, whilst Kaneshie market (67.5%) had the least. Present study revealed that mixed infection with gastrointestinal parasites of different species was more common than infection with single species in chickens in Accra.